(untitled) (Revista Iberoamericana de Bioética, 2022)
This study delves into the possibilities for women patients receiving palliative care in times of health emergencies when in-person care becomes dilemmatic. Based on the bibliography compiled and testimonies from key public health informants, the problems are described among this population. The COVID-19 pandemic context and suspension of face-to-face care are analysed among this sample. The objective is to evaluate whether or not telehealth is an efficient substitute for face-to-face consultations during health emergencies with restrictive decrees on people’s movements, such as forced lockdowns and social isolation, and whether it widens the gap in access to healthcare. The conclusion drawn is that the difficulties these patients described only grew due to virtual care, and their rights were exponentially violated. Finally, a suitable care protocol is proposed for this group of women.